Influence of academic self-concept and academic achievement motivation on Faculty of Education UTM postgraduates' academic performance - Teo, Eyu Li (2011)
The purpose of this study was to find out the influence of academic self-concept and academic achievement motivation on Faculty of Education (FP) UTM postgraduates’ academic performance. This study discovered the level of academic self-concept and the level of academic achievement motivation of FP UTM postgraduates. It also investigated the gender and age differences in academic self-concept, as well as the gender and age differences in academic achievement motivation among FP UTM postgraduates. Respondents of this study were master degree postgraduates from Faculty of Education UTM. The sampling method employed was stratified sampling. Questionnaires were distributed to 250 respondents but only 215 sets of completed questionnaires were collected back. Data collected was organized and analyzed using the Statistical Package for Social Science (SPSS) version 16.0 for Windows. The level of academic self-concept among FP UTM postgraduates were measured using related items in the Self-Descriptive Questionnaire (SDQ) III for late adolescents and young adults developed by Herbert William Marsh (1990). The level of academic achievement motivation of FP UTM postgraduates were measured using related items in the Deo-Mohan Achievement Motivation Scale developed by Pratibha Deo and Asha Mohan (1985). From the pilot test, internal consistency reliability for the overall items revealed a coefficient alpha value of 0.83. Independent Samples t-test found that there were significant difference of academic self-concept and academic achievement motivation among FP UTM postgraduates based on gender. Females scored higher than males in both academic self-concept and academic achievement motivation. One-way Analysis Covariance (ANOVA) found out that there was no significant difference in academic self-concept and academic achievement motivation among FP UTM postgraduates based on age. The influence of academic self-concept and academic achievement motivation towards academic performance was found out using Simple Regression Analysis. Findings revealed that academic self-concept had a weak positive influence on academic performance. Person’s Coefficient Correlation was used to analyse the correlation between academic selfconcept and academic achievement motivation. Results showed a significant and moderate correlation between academic self-concept and academic achievement motivation among FP UTM postgraduates.